Errores conceptuales en el estudio del equilibrio químico: nuevas aportaciones relacionadas con la incorrecta aplicación del principio de Le Chatelier - Quílez Pardo, J.; Sanjosé López, V. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
The limited usefulness of the Le Chatelier's principie and its vague and ambiguous formulation may be some of the sources of misconceptions in chemical equilibrium. To diagnose misconceptions a written test was administered to 170 first -year students. Responses revealed that mistakes emerged through: a) misapplication and misunderstanding of the Le Chatelier's principle; 12) utilization of rote -learning recall and algorithmic procedures, c) incorrect control of the variables involved and limited use of the chemical equilibrium law; d) tack of mastery of the principles of chemical equilibrium and difficulty in transfering them to new situations.